Antimicrobial resistance and universal health coverage. Issue 4 (31st October 2017) - Bloom, Gerald; Merrett, Gemma Buckland; Wilkinson, Annie; Lin, Vivian; Paulin, Sarah
Abstract : The WHO launched a Global Action Plan on antimicrobial resistance (AMR) in 2015. World leaders in the G7, G20 and the UN General Assembly have declared AMR to be a global crisis. World leaders have also adopted universal health coverage (UHC) as a key target under the sustainable development goals. This paper argues that neither initiative is likely to succeed in isolation from the other and that the policy goals should be to both provide access to appropriate antimicrobial treatment and reduce the risk of the emergence and spread of resistance by taking a systems approach. It focuses on outpatient treatment of human infections and identifies a number of interventions that would be needed to achieve these policy goals. It then shows how a strategy for achieving key attributes of a health system for UHC can take into account the need to address AMR as part of a UHC strategy in any country. It concludes with a list of recommended priority actions for integrating initiatives on AMR and UHC.